Lexicographic Multi-objective Optimisation of Hybrid Power Generation Systems for Communities in Non-Interconnected Zones - Ojeda Camargo, Edgar; Candelo-Becerra, John E.; Mercado, Alcides Santander (International Journal of Energy Economics and Policy, 2019)
Energy supply applications for populations in isolated areas have great importance in reducing poverty and environmental impacts. However, rural zones not connected to power grids require more studies related to select low cost and efficient technologies suitable to each size of community. This paper presents a lexicographic multi-objective optimisation model (LMOM) to select the best renewable energy technologies (solar and wind) of hybrid power generation systems (HPGSs) for communities located in non-interconnected zones. The model prioritises objective functions such as the generation cost, emissions of carbon dioxide (CO2) and energy consumption in ton-equivalent petroleum (TEP). In addition, the model considers constraints related to the production cost, environmental sustainability, environmental conditions and reliability of the system. The results show that the model provides sustainable HPGSs adapted to the size of each community and the best renewable energy technologies are the central receiver system and the wind turbine with a 20-metre tower. Keywords: Renewable Energy, Rural Communities, Multi-objective Optimization JEL Classifications: C61, Q42 DOI: https://doi.org/10.32479/ijeep.7574